Modern Talaqqi Method: Innovation in Turats Learning in Islamic Boarding Schools - Alif Qurrotin; Martoyo Martoyo (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
The talaqqi method is a traditional approach typical of Islamic boarding schools in learning turats books that emphasizes direct relations between kiai and students. However, developments in the era, especially in the digital era, demand innovation so that this method remains relevant for the millennial generation of students. This study aims to identify innovations in the talaqqi method, assess its effectiveness in improving understanding of yellow books, and formulate a digital-humanistic learning model that maintains classical values ​​but is technology-based. With a qualitative approach and multi-case studies in several Islamic boarding schools, data were obtained through observation, in-depth interviews, and documentation. The results of the study show that innovation through digital media, e-learning, and interactive approaches can improve the competence of students and expand the preservation of turats. This transformation does not eliminate the essence of talaqqi, but rather contextualizes its values ​​in a more modern and inclusive form. Thus, Islamic boarding schools can play a strategic role as preservers of Islamic heritage as well as agents of change in contemporary education.